The potential therapeutic effects of creatine supplementation on body composition and muscle function in cancer. (January 2019) - Fairman, C.M.; Kendall, K.L.; Hart, N.H.; Taaffe, D.R.; Galvão, D.A.; Newton, R.U.
Graphical abstract: Highlights: Muscle loss in cancer has profound physical and psychological impacts. Creatine has been shown to enhance muscle mass in clinical populations. Individuals at increased risk of muscle loss may benefit the most from creatine. Abstract: Low muscle mass in individuals with cancer has a profound impact on quality of life and independence and is associated with greater treatment toxicity and poorer prognosis. Exercise interventions are regularly being investigated as a means to ameliorate treatment-related adverse effects, and nutritional/supplementation strategies to augment adaptations to exercise are highly valuable. Creatine (Cr) is a naturally-occurring substance in the human body that plays a critical role in energy provision during muscle contraction. Given the beneficial effects of Cr supplementation on lean body mass, strength, and physical function in a variety of clinical populations, there is therapeutic potential in individuals with cancer at heightened risk for muscle loss. Here, we provide an overview of Cr physiology, summarize the evidence on the use of Cr supplementation in various aging/clinical populations, explore mechanisms of action, and provide perspectives on the potential therapeutic role of Cr in the exercise oncology setting.